Coexistence of Tellurium Cations and Anions in Phosphonium-Based Ionic Liquids - Grasser, Matthias A.; Pietsch, Tobias; Blasius, Jan; Holloczki, Oldamur; Brunner, Eike; Doert, Thomas; Ruck, Michael (Chemistry - A European Journal, 2022)
Elemental tellurium readily dissolves in ionic liquids (ILs) based on tetraalkylphosphonium cations even at temperatures below 100 °C. In the case of ILs with acetate, decanoate, or dicyanamide anions, dark red to purple colored solutions form. A study combining NMR, UV-Vis and Raman spectroscopy revealed the formation of tellurium anions (Ten)2− with chain lengths up to at least n=5, which are in dynamic equilibrium with each other. Since external influences could be excluded and no evidence of an ionic liquid reaction was found, disproportionation of the tellurium is the only possible dissolution mechanism. Although the spectroscopic detection of tellurium cations in these solutions is difficult, the coexistence of tellurium cations, such as (Te4)2+ and (Te6)4+, and tellurium anions could be proven by cyclic voltammetry and electrodeposition experiments. DFT calculations indicate that electrostatic interactions with the ions of the ILs are sufficient to stabilize both types of tellurium ions in solution.
CRIS-Team Scopus Importer:2022-04-14